Barriers in adopting blended learning in a private university of Pakistan and East Africa: faculty members’ perspective - Rizvi, Nusrat Fatima; Gulzar, Saleema; Nicholas, Wachira; Nkoroi, Beatrice (mHealth, 2017)
Background: Education methods have undergone transformation over the centuries. Use of technology is the cornerstone for innovation in teaching methods. Hence, blended learning which includes face to face and online modalities is being increasingly explored as effective method for learning. This pilot study determines the perceptions of faculty members in a private international university on barriers influencing adoption of technology for teaching and learning. Methods: A cross-sectional survey was conducted through a self-reported questionnaire using ‘survey monkey’. The data was entered and analyzed using Statistical Package for the Social Sciences (SPSS version 20). Frequencies and proportions are reported. Results: Findings indicated that 51.6% faculty members perceived the importance of integration of technology in their teaching. Around 54% of the participants recognized that they do possess the ability and accessibility to integrate information communication technology (ICT) in teaching and learning, but there is a need to hone the basic information technology (IT) skills to initiate technology driven teaching. Findings revealed that 55% faculty members acknowledged the constraint of not getting protective time to develop and deliver technology driven courses. Further, results showed that 45% faculty members perceived that their innovation efforts in terms of teaching as blended learning do not count towards their professional promotion or recognition, as usually priority is given to research over teaching innovation. The findings also indicated that 54.5% participants asserted that university lack mentorship in the field of blended learning. Conclusions: Therefore, study suggests that universities should provide adequate mentorship programmes for the faculty members in enhancing their skills of integrating technology in their teaching.